The Impact of the Distribution of Zakat Funds on Poverty Alleviation in Indonesia - Faizah, Nur; Haryono, Slamet (ZISWAF, 2025)
Abstract: Poverty is still a major problem in Indonesia, therefore an effective and comprehensive strategy is needed. Zakat is considered to be able to overcome the problem of poverty because it directly involves the structure of the community. This study aims to empirically investigate the impact of zakat distribution on poverty alleviation both in quantity and quality by using the BAZNAS Welfare Index (IKB) of 8 provinces that have the highest percentage of poor people in Indonesia. This research uses panel data method with REM analysis. The result of this study is that the distribution of zakat funds has a significant effect on reducing the number of poor people (P0). A panel data approach with REM analysis is used in this study. This study's conclusion is that there are much fewer impoverished individuals (P0) as a result of the distribution of zakat payments. But, at the provincial level, zakat (IKB) has no discernible impact on the degree of poverty depth (P1) or poverty severity (P2).l.